A general equilibrium analysis of China's urbanization. Issue 3 (3rd July 2018) - Zhang, James Xiaohe
ABSTRACT: One of the issues of rapid urbanization in China is how the liberalization of factor markets will impact its economy. Based on a general equilibrium theoretical framework, this paper develops some hypotheses including that while the removal of the household registration system would generate unambiguous welfare gains, the land reform may have some modest impact on income redistribution. These theoretical hypotheses are examined with some empirical statistical data and simulation experiments based on a computable general equilibrium model (the GTAP model) in which several different policy scenarios including reforms in both labour and land markets are considered.